Survey on Economical Important Fungal Diseases of Tomato in Sub-Zoba Hamemalo of Eritrea - Naqvi, Syed Danish Yaseen; Tesfalem, Awet; Tesfazghi, Bereket; Asfeha, Gezae; Mangesteab, Ruta (Review of Plant Studies, 2014)
Hamelmalo region. Through the survey, 4 diseases namely, early blight, late blight, powdery mildew and wilt and 2 insects: Helicoverpa armigera and Tuta absoluta were recorded. The main objective of the study was to undertake survey for the incidence of early blight and powdery mildew of tomato caused by Alternaria solani and Oidium neolycopersici respectively. The maximum disease incidence due to early blight was 56.28% in F5 and minimum was 19.05% in seven days interval during survey whereas in case of powdery mildew the maximum and minimum was 38.96% in F2 and 13.43% in F5 respectively. Overall average for higher leaf infection in early blight and powdery mildew of tomato were recorded 41.85% and 34.63%, respectively. The average of disease complex incidence of 71.6% and 62.60% was recorded in F6 and F4, respectively.